Students’ Perception on Plagiarism - Mika Hatigoran Manalu (Universitas Pendidikan Indonesia (UPI), 2013)
This research is intended to find out how far college students’ knowledge within act of plagiarism. Also, the issue of plagiarism was lifted to the surface because issues of plagiarism that have been revealed to the public is spread rapidly. One of the main reasons why plagiarism exists because teaching processing in classroom doesn’t care on this issue. In this research, respondents were given a questionnaire that consists of 20 questions. Analysis of completed questionnaire showed student uncertainty about several aspects of plagiarism. Though, the media has given attention to plagiarism, students are not always aware of the limitation between plagiarism and proper academic writing. Perhaps, some information about penalties of plagiarizing should be told to students to make them more aware about this act of cheating. Keywords: Plagiarism, Questionnaire, Students, College, Penalty, Academic Writing